2021
DOI: 10.3389/fmed.2020.615997
|View full text |Cite
|
Sign up to set email alerts
|

Acute Functional Outcomes in Critically Ill COVID-19 Patients

Abstract: Background: COVID-19 (Coronavirus Disease 2019) is a global cause of morbidity and mortality currently. We aim to describe the acute functional outcomes of critically ill coronavirus disease 2019 (COVID-19) patients after transferring out of the intensive care unit (ICU).Methods: 51 consecutive critically ill COVID-19 patients at a national designated center for COVID-19 were included in this exploratory, retrospective observational cohort study from January 1 to May 31, 2020. Demographic and clinical data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 35 publications
1
9
1
Order By: Relevance
“… 32 , 33 , 51 , 52 Notably, functional mobility decline in our cohort was primarily attributable to impaired gait independence. Two previous studies found that 83–92% of COVID-19 survivors were discharged from hospital as autonomous walkers 32 , 53 in contrast to the 45.7% of independent walkers in our cohort. Differences in effectiveness of local rehabilitation practices, longer length of stay in acute wards and the specific ceiling effects of the varying outcome measures used may have all contributed to this disparity.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“… 32 , 33 , 51 , 52 Notably, functional mobility decline in our cohort was primarily attributable to impaired gait independence. Two previous studies found that 83–92% of COVID-19 survivors were discharged from hospital as autonomous walkers 32 , 53 in contrast to the 45.7% of independent walkers in our cohort. Differences in effectiveness of local rehabilitation practices, longer length of stay in acute wards and the specific ceiling effects of the varying outcome measures used may have all contributed to this disparity.…”
Section: Discussioncontrasting
confidence: 77%
“…This is in agreement with recent work showing reduced acute functional status in invasively ventilated COVID-19 patients. 29,51,53 Previous studies in ARDS survivors and other critically ill patient populations also found that these are poor prognostic factors for long-term physical decline. 58,59 Early recognition of patients most at-risk of functional mobility decline, and support with advance care planning and targeted rehabilitation interventions may help improve long-term outcome in COVID-19 survivors.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with previous research, we observed that COVID-19 ICU patients are prone to ICUAW at ICUand hospital discharge, defined as a MRC-SS ≤48 [1,[10][11]. Furthermore, we showed that compared to other pneumosepsis patients, COVID-19 patients scored lower on physical functioning tests upon ICU discharge.…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with previous research, we observed that COVID‐19 ICU patients are prone to ICUAW at ICU and hospital discharge, defined as an MRC‐SS of ≤48. 1 , 10 , 11 Furthermore, we showed that compared with other pneumosepsis patients, COVID‐19 patients scored lower on physical functioning tests upon ICU discharge. Contrastingly, COVID‐19 patients showed significantly more improvement of physical functioning on the MRC‐SS and the CPAx instruments during post‐ICU hospital stay, regardless of baseline characteristics, adequacy of protein administration during ICU stay, and duration of ward LOS.…”
Section: Discussionmentioning
confidence: 70%
“…Similarly, post-intensive care syndrome (PICS) has been described after shock, sepsis, hypoxia, ARDS or delirium, significantly increasing the risk of long-term cognitive and physical impairment [ 47 , 48 ]. Longer-term studies with follow-up and control groups are warranted to shed light on this aspect [ 49 51 ].…”
Section: Discussionmentioning
confidence: 99%